Screening of gestational diabetes mellitus in early pregnancy by oral glucose tolerance test and glycosylated fibronectin: study protocol for an international, prospective, multicentre cohort trial. Issue 10 (12th October 2016) - Huhn, E A; Fischer, T; Göbl, C S; Todesco Bernasconi, M; Kreft, M; Kunze, M; Schoetzau, A; Dölzlmüller, E; Eppel, W; Husslein, P; Ochsenbein-Koelble, N; Zimmermann, R; et al.
Abstract : Introduction: As the accurate diagnosis and treatment of gestational diabetes mellitus (GDM) is of increasing importance; new diagnostic approaches for the assessment of GDM in early pregnancy were recently suggested. We evaluate the diagnostic power of an 'early' oral glucose tolerance test (OGTT) 75 g and glycosylated fibronectin (glyFn) for GDM screening in a normal cohort. Methods and analysis: In a prospective cohort study, 748 singleton pregnancies are recruited in 6 centres in Switzerland, Austria and Germany. Women are screened for pre-existing diabetes mellitus and GDM by an 'early' OGTT 75 g and/or the new biomarker, glyFn, at 12–15 weeks of gestation. Different screening strategies are compared to evaluate the impact on detection of GDM by an OGTT 75 g at 24–28 weeks of gestation as recommended by the International Association of Diabetes and Pregnancy Study Groups (IADPSG). A new screening algorithm is created by using multivariable risk estimation based on 'early' OGTT 75 g and/or glyFn results, incorporating maternal risk factors. Recruitment began in May 2014. Ethics and dissemination: This study received ethical approval from the ethics committees in Basel, Zurich, Vienna, Salzburg and Freiburg. It was registered under http://www.ClinicalTrials.gov (NCT02035059 ) on 12 January 2014. Data will be presented at international conferences and published in peer-reviewed journals. Trial registration number: NCT02035059.